Family Support Affect Bonding Attachment of Baby and Adolescent Mother - Puspasari, Jehan; Larasati, Lela; Winarti, Retno (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
AbstractThe transition to parenthood can be difficult for adolescent. The birth of a baby causes a fundamental challenge to the interaction structure that has been formed. Mothers have a very important role in improving health status, especially in terms of monitoring the growth and development of babies. Unpreparedness in carrying out her new role as a mother can cause frustration and perceive her baby as a nuisance and can be psychological disorders such as postpartum depression or postpartum blues, thereby reducing the bond between mother and baby. This study used a cross-sectional method with a purposive sampling technique on 106 respondents. The results of univariate analysis showed that the average age of teenage mothers was 18 years, marital status was married (90.56%), last education was high school (81.14%), the baby's temperament was difficult (66.9%) and the mother's psychosocial condition was not at risk (54%). Bivariate analysis shows that family support influences the bond between babies and adolescent mothers, with informational support of 86.1%, instrument support of 90%, emotional support of 76.5% and appreciation support of 78.2%. The results of this study it can be concluded, the good family support, can affect the better of bonding attachment between mother and baby.Keywords:  Adolescent Mothers, Family Support, Bonding Attachment